The Tradition of Milet Kandung: A Local Wisdom Perspective In Neuroscience and Islamic Law In Madura - Jailani, Mohammad (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study examines the Milet Kandung tradition in Pasean, Pamekasan, Madura, from the perspectives of neuroscience and Islamic law. The main objective is to analyze how this tradition reflects local wisdom and neurospiritual practices within an Islamic context. The research employs a qualitative case study approach, utilizing fieldwork methods such as interviews and observations. Initial findings suggest that Milet Kandung embodies a form of normative piety, intertwining spiritual practices with the community’s cultural heritage. From a neuroscience standpoint, the ritual is seen to influence neurospiritual states, reinforcing emotional and cognitive connections to faith. The Islamic legal perspective highlights the tradition’s alignment with ethical and religious values, affirming its role in preserving communal harmony. The study concludes that Milet Kandung represents a synthesis of local wisdom, neurospirituality, and Islamic principles, contributing to the socio-religious identity of the Madurese people.